Durability Consideration Of Expanded Polystyrene (EPS) Concrete - Su, Kenneth Swee Kwang (Universiti Malaysia Sarawak (UNIMAS), 2009)
The results of the study on the appropriate miz proportions of Expanded Polystyrene (EPS) concrete is presented. The study mainly to investigate the mix proportions of EPS concrete with various percentages of EPS aggregate replaced with normal weight aggregates to obtain the lowest water absorption.